Winter breeding and high tadpole densities may benefit the growth and development of tadpoles in a subtropical lowland treefrog. (16th July 2014) - Chang, Y.‐M.; Tseng, W.‐H.; Chen, C.‐C.; Huang, C.‐H.; Chen, Y.‐F.; Hatch, K. A.
Abstract Unlike high‐altitude Rhacophorus moltrechti breeding in spring and summer and middle‐altitude populations breeding throughout the year, one possible mechanism causing lowland populations to breed in winter may be that high summer temperatures at low altitudes are stressful for tadpoles and lowland populations so they breed in winter to avoid this stress. However, breeding in the winter, which is the dry season in Taiwan, causes high densities as the water bodies they breed in are smaller and more isolated. We tested whether high summer water temperatures impose a cost and high tadpole densities lead to a benefit in growth, development and survival of lowland tadpoles by rearing tadpoles at three temperatures (17 and 22°C are two typical winter water temperatures and 27°C is a representative summer water temperature) and four different densities (5, 10, 20 and 30 tadpoles per box). We found that tadpoles metamorphosed earlier and at smaller sizes at 22°C (the higher winter water temperature) than tadpoles raised at either 17 or 27°C. Tadpoles raised at 27°C exhibited a longer larval period and a smaller metamorphic size than those raised at 22°C. Likewise, under the two winter water temperatures, but not the summer water temperature, increased tadpole density enhanced larval growth, translating into greater metamorphic mass without changing time to metamorphosis or decreasing survival rates. Nevertheless, tadpoles survived to metamorphosis at 27°C and at rates equal to those at 17 and 22°C. Our study suggests that lowland tadpoles are better adapted to maturing at cooler, winter water temperatures and that the summer water temperatures may be stressful to their growth and development. This leads to winter breeding for lowland populations. It also suggests that lowland populations breed at high tadpole densities because high densities benefit the larval growth and development.